Micromachine for Locomotion Inside Pipe - Mikova, Lubica; Virgala, Ivan; Kelemen, Michal; Liptak, Tomas; Hroncova, Darina (Communications - Scientific letters of the University of Zilina, 2018)
The paper deals with miniature machine for locomotion inside pipe. It uses impact energy as a principle of motion. Dynamics description and simulation model has been created. The deviations of the features are resulting from the fact that within the simulation model the friction between the bristle and the pipe wall is presented through the model not regarding the variability of the friction force and existing geometric deviations of the pipe inner surface.